Activation of Dangerous Natural Processes on the Territory of the Kabardino-Balkarian and Karachay-Cherkess Republics - Kyul Elena; Gedueva Maryana; Kondratyeva Natalia; Baidaeva Zuleyha (Russian Journal of Earth Sciences)
The paper considers the manifestations of dangerous natural processes and their consequences in the territories of two republics – the Kabardino-Balkarian and Karachay-Cherkess Republics for the period from 2015 to 2022. On the basis of the collected material, an analysis of the manifestations of hazardous natural processes was carried out and maps-schemes were compiled.